The Role of Television Program in Supporting Social Responsibility Analytical Descriptive Study for "Pain and Hope Program" in Al Sharjah Satellite Channel (International Journal of Psychosocial Rehabilitation, 2020)
This study has tried to investigate the role of television programs in supporting the values of social responsibility, shaping the good impression of these satellite channels towards society, achieving its message in serving society’s issues, and reflecting successful experiences to challenge difficulties.